Impact of Congenital Cardiac Catheterization Project on Outcomes-Quality Improvement (C3PO-QI) in LMICs. Issue 1 (10th January 2019) - Ali, Fatima; Qasim Mehdi, Mohammad; Akhtar, Saleem; Aslam, Nadeem; Abbas, Rashid; Shah, Izat; Abidi, Jabbir; Arthur, Sajid; Nizar, Zeenat; Goodmann, Andrea; Bergersen, Lisa; Hasan, Babar
Abstract : Background: The importance of registries for collaborative quality improvement has been overlooked in low/middle-income countries (LMIC). Aga Khan University Hospital (AKUH) in Pakistan joined the Congenital Cardiac Catheterization Project on Outcomes-Quality Improvement (C3PO-QI) in March 2017 with the goal of leveraging international collaboration to improve patient care and institutional standards. Methods: The C3PO-QI key driver-based approach was used, with certain modifications, for process re-engineering in AKUH's congenital cardiac catheterisation laboratory (CCL) to reduce radiation exposure during cardiac catheterisation procedures (the primary outcome of C3PO- QI). Educating staff and standardising procedural documentation were the principal goals of the process re-engineering. Data survey was used to assess staff knowledge, attitude and practice before and after the initiative. Additionally, case demographics and outcomes were compared between AKUH and C3PO-QI centres. Results: There was an increase in appropriate recording of radiation surrogates (0%–100%, p=0.00) and in the percentage of cases that met the established benchmark of 'Ideal documentation' (35% vs 95%, p=0.001). There was also an increase in self-reported staff interest during the case (25% vs 75%, p=0.001). AKUH versus C3PO-QI data showed similar demographic characteristics. There was a slight over-representation of diagnostic cases (42% vs 32%) as compared with interventional (58% vs 68%) at AKUH. Furthermore, interventional procedures were predominately PDA and ASD device closures (n=19 and 15, respectively). The frequency of adverse events were the same between AKUH and collaborative sites. Conclusion: Collaborative efforts between developed and LMIC CCL are significant in advancing system-level processes.